(untitled) (Al-Academy, 2021)
The research deals with the concept of stigma as one of the important phenomena that cast a shadow over the nature of the individual, his being and his personality through the inferior view with which he confronts in society, and (Sartors) indicates in this regard that stigma may lead to negative discrimination that leads to many defects, in terms of obtaining On care, poor health, service, and frequent setbacks that can damage self-esteem. The first roots of this phenomenon go back to the Greek civilization and what the Greeks used to burn and cut off some parts of the body and then announce to the nation that the bearer of this sign is a criminal. In addition to the Arab peoples living from setbacks that contributed to the exacerbation of this phenomenon, especially as we live in a society that has suffered a lot Wars and the consequences it has produced in the life of the individual and society, and given the privacy that theater enjoys in terms of communication and reception, this study came to shed light on the phenomenon of stigmatization. This study included the introduction of the research in which the researcher presented the research problem, its importance and its goal. Then the theoretical framework that dealt with a theoretical foundation for the research included two topics: the concept of stigma and the second: representations of stigma in the international theatrical text. The researcher came up with a set of indicators that I adopted in the analysis of the research sample model. After the analysis, the two researchers came up with a set of results, including: The study model was characterized by its presentation of social stigma through its statement of the individuals’ dissatisfaction and ridicule of the Sultan’s personality as a slave rather than a free person, which constituted a kind of social lack of acceptance and caused a danger in the issue of continuing the ruling